Hierarchical Porous Monoliths of Steel with Self‐Reinforcing Adaptive Properties. Issue 10 (25th January 2023) - Carpenter, Julia A.; Saraw, Zoubeir; Schwegler, Alain; Magrini, Tommaso; Kuhn, Gisela; Rafsanjani, Ahmad; Studart, André R.
Abstract: Porous structures offer an attractive approach to reduce the amount of natural resources used while maintaining relatively high mechanical efficiency. However, for some applications the drop in mechanical properties resulting from the introduction of porosity is too high, which has limited the broader utilization of porous materials in industry. Here, it is shown that steel monoliths can be designed to display high mechanical efficiency and reversible self‐reinforcing properties when made with porous architectures with up to three hierarchical levels. Ultralight steel structures that can float on water and autonomously adapt their stiffness are manufactured by the thermal reduction and sintering of 3D printed foam templates. Using distinct mechanical testing techniques, image analysis, and finite element simulations, the mechanisms leading to the high mechanical efficiency and self‐stiffening ability of the hierarchical porous monoliths are studied. The design and fabrication of mechanically stable porous monoliths using iron as a widely available natural resource is expected to contribute to the future development of functional materials with a more sustainable footprint. Abstract : Porous steel structures combining ultralow weight and high mechanical efficiency are manufactured by printing, reducing, and sintering wet foams containing iron oxide precursor particles. By forming new load‐bearing struts when compressed, the porous structures are able to reversibly stiffen in response to nonuniform stresses, a behavior that conceptually resembles the unique adaptive properties of human bone.